THERMO-CURED GLASS IONOMER CEMENTS IN RESTORATIVE DENTISTRY - Kristina GORSETA; Domagoj GLAVINA (Journal of Istanbul University Faculty of Dentistry, 2017)
Numerous positive properties of glass ionomer cements including biocompatibility, bioactivity, releasing of fluoride and good adhesion to hard dental tissue even under wet conditions and easy of handling are reasons for their wide use in paediatric and restorative dentistry. Their biggest drawbacks are the weaker mechanical properties. An important step forward in improving GIC’s features is thermo-curing with the dental polymerization unit during setting of the material. Due to their slow setting characteristics the GIC is vulnerable to early exposure to moisture. After thermo curing, cements retain all the benefits of GIC with developed better mechanical properties, improved marginal adaptation, increased microhardness and shear bond strength. Adding external energy through thermocuring or ultrasound during the setting of conventional GIC is crucial to achieve faster and better initial mechanical properties. Further clinical studies are needed to confirm these findings.